(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The port of Lattakia is particularly important because it is one of the most important ports in the eastern basin of the Mediterranean Sea as a base for international multimodal transport in the Arab East, which is one of the most active marine basins in the world. The port is associated to Hinterland back with neighboring countries where goods are transported by land through border and international ports and across the sea different parts of the world, and prepare The study of the ground field (Hinterland) and the sea field (Foreland) of ports are important subjects which show us the importance of the port and its internal and external relations, and what it provides of supplies which reflects one of the most important sources of national income. The study of the Hinterland and the foreland that shows us the extent of the relationship Between the port and the outside world and the geographical orientation of the port through its exports and imports and the extent of the influence of its influence is shown in the maps of its contact with all continents of the world.